Current Approaches to Phonological Theory - Dinnsen, Daniel A. (Indiana University Press, 1979)
Since the advent of generative phonology, linguists have turned their attention to elaborating or constraining the 'standard theory'. The present volume, the outgrowth of a conference held at Indiana University in the fall of 1977, engages in dialogue the leading proponents of some of the most stimulating current approaches to phonological theory and makes possible a serious and systematic comparison of their views. Some of the larger questions taken up in this volume are: What specific issues or problems have given rise to each new theoretical approach to force a depature from 'standard theory'? How do the new approaches differ from one another? What aspects of these differences are formal/empirical? Are there any bases for judging one theory or approach to be superior to another?